2020
DOI: 10.1017/s1754470x20000240
|View full text |Cite
|
Sign up to set email alerts
|

Therapy discontinuation in a primary care psychological service: why patients drop out

Abstract: The present study aimed to explore patients’ experience with an Improving Access to Psychological Therapies (IAPT) service, and to investigate the reasons for discontinuing their treatment. A qualitative approach was adopted using thematic analysis of semi-structured interviews carried out with 818 patients attending for treatment in Talking Change from November 2015 to January 2019, retrospectively. The five main themes that emerged from the study were: ‘Felt better’, ‘Issues with group settings’, ‘Therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…According to the therapists, the principal reason for termination was dropout. The dropout rate (47.8%) was consistent with other studies-the reported dropout rate in psychotherapy ranges from 30% to 60% (Ghaemian et al, 2020;Wang, 2007;Wierzbicki & Pekarik, 1993).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to the therapists, the principal reason for termination was dropout. The dropout rate (47.8%) was consistent with other studies-the reported dropout rate in psychotherapy ranges from 30% to 60% (Ghaemian et al, 2020;Wang, 2007;Wierzbicki & Pekarik, 1993).…”
Section: Discussionsupporting
confidence: 89%
“…Studies have found that dropout should not always be associated with poorer outcomes (O'Keeffe et al, 2019), and some studies have highlighted the fact that patients may feel better in spite of dropping out of treatment (Ghaemian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Patient feedback was transcribed at the point of collection. The transcriptions obtained from January 2016 to January 2017 were collated, and a thematic analysis was conducted (see Ghaemian et al, 2020).…”
Section: Identifying Factors Of Readiness For Therapymentioning
confidence: 99%
“…Data transparency. Three of the current authors of this manuscript have published a qualitative paper (Ghaemian et al, 2020), where the data have been extracted from the same sample as this manuscript, albeit with a different focus. The current manuscript is looking at the validity of RTQ and whether or not RTQ can predict outcome and drop-out, whereas the qualitative paper is focusing on patients' subjective experience of therapy and reasons for discontinuation from therapy.…”
mentioning
confidence: 99%
“…Delgadillo et al (2016) found significant outcome variability between large didactic psychoeducational groups despite the intervention being manualized (White and Keenan, 1990), and so called for more research evaluating the effectiveness of group LI interventions that concurrently measured the competency and fidelity of practitioners to LI treatment protocols. Ghaemian et al (2020) noted that these large psychoeducational groups can be difficult to manage, with practitioners also needing good teaching skills to deliver the psychoeducational content in an easy-to-understand manner.…”
Section: Introductionmentioning
confidence: 99%